(untitled) (Bioagro, 2026)
The new potato clones, biofortified with iron and zinc, represent a very valuable alternative to help combat anemia in the population. However, they require further evaluation in their postharvest behavior. The objective of this research was to evaluate the postharvest behavior in 12 of these new clones, along with two commercial varieties. After cultivation of the crop in the Viñac, Gorgor and Checras districts of the Lima region - Perú, tubers were harvested, and an independent experiment was conducted in each location evaluating 14 genotypes, with three repetitions. Weight loss, sprouting, dormancy and greening of the tubers were evaluated periodically between 30 and 150 days of storing. Only two of the 12 clones showed a dormancy period slightly longer than 60 days in the Viñac location. In general, clones BIOT-767.014 and BIOT-725.050 showed low weight loss and a convenient low sprouting with apical dominance for the total storage period, so both were considered among the best in the groups. Additionally, BIOT-725.050 stood out because it had the lowest greening. It is concluded that clones BIOT-767.014 and BIOT-725.050 are promising materials because they present low postharvest weight loss, as well as low sprouting and low degree of greening.